Sealing of near-surface voids on cement concretes by combined application of metal-ethylenediaminetetraacetic acid complex solutions and high-heat treatment via hydrogen/oxygen coupled flame. (27th September 2021) - Kudo, Takuya; Komatsu, Keiji; Nakamura, Atsushi; Ito, Osamu; Suzuki, Atsuko; Yamamura, Mirai; Shimomura, Takumi; Saitoh, Hidetoshi
Highlights: The calcium aluminates were fabricated on mortar substrates using (Ca-Al)-EDTA solutions, followed by high-heat treatment with a H2-O2 coupled flame. The permeability was reportedly improved compared with the mortar itself. The pore distributions in the mortar was changed, and shifted to smaller pore sizes. A sealing process model combining metal-EDTA complex solutions and high-heat treatment was comprehensively proposed. Abstract: Near-surface voids on a cement concrete sample were successfully sealed by applying a metal-ethylenediaminetetraacetic (EDTA) acid complex solution, followed by treatment with high-heat hydrogen/oxygen (H2 -O2 ) coupled flame. The calcium aluminates used for sealing were fabricated on cement substrates using calcium-aluminate (Ca, Al)-EDTA solutions prepared at various elemental ratios. The sealing effects were investigated through crystal & pore structure analysis and water permeability tests, using X-ray computed tomography (X-CT). Existence of the calcium aluminates were confirmed. From X-CT analysis, the average void diameter was changed from 16 μm to 10 μm with the calcium aluminate's sealing. A sealing process model combining metal-EDTA complex solutions and high-heat treatment, intended for the surface sealing of cement concretes used in construction, was comprehensively proposed.